Bacterial profile and antimicrobial sensitivity pattern of pus in Dhaka National Medical Institute Hospital (Journal of Dhaka National Medical College & Hospital, 2015)
Objectives: To assess the causative bacteria and antibiotic sensitivity pattern of different bacteria isolated from pus.Methods: This cross-sectional study was conducted from January to December, 2014 to assess the bacterial profile isolated from pus from the patients of Microbiology department of Dhaka National Medical Institute Hospital. Data were collected by interviewer administered questionnaire. The pus was collected by sterile cotton swab. Bacteria were cultured and sensitivity pattern was examined. Results: A total of 149 patients were included in this study with the average age of 32.5 years. More than half of them (64.4%) were female. Half of the respondents (49.7%) were admitted in hospital. Higher portion of the respondents had history of operative treatment under surgery (44%), gynecology (36%) and other departments. Higher portion (30%) of the specimens was collected from abdomen. Among 149 isolates, organisms were revealed from 112 (75%) specimens. S. aureus was the most frequently isolated bacteria constituting 55 (49%) isolates, followed by E. coli 23 (20.5%) isolates. Gram positive bacteria were highly sensitive to vancomycin, linezolid and fusidic acid. They were resistant to amoxicillin and ceftazidine. Gram negative bacteria were highly sensitive to amikacin, imipenem&tazopiperacillin. They showed resistance to amoxicillin, cephradine, cefuroxime and cotrimoxazole.Conclusion: Pus was caused predominantly by Gram positive organism specially S. aureus. The bacteria were showing resistant to popular antibiotic. Appropriate antibiotic coverage is needed to avoid development of the resistant organismsJ.Dhaka National Med. Coll. Hos. 2015; 21 (02): 19-23